A nation with the soul of a church : how Christian proclamation has shaped American history - Edwards, O. C. (Otis Carl), 1928- (Santa Barbara, California : Praeger, 2013)
"From the very beginning, religious leaders have influenced the course of American history--sometimes for better, sometimes for worse. This book examines those Christian sermons that set or changed the course of the nation"--
"A modell of Christian charity": John Winthrop (1588-1649) -- "Our God sent a new storm": Anne Hutchinson -- "The limit of endurable ecstasies": Jonathan Edwards -- The tolerable catechist: Jonathan Mayhew -- "The impassioned little saint with the buring heart": William Ellery Channing -- "The cultural priest and visionary": Ralph Waldo Emerson -- "I am a South Carolinian, you know": Benjamin Morgan Paqlmer -- "In the next generation, I shall be orthodox enough": Henry Ward Beecher -- "The penniless millionaire": Russell H. Conwell -- A social evangelist: Washington Gladden -- Casting out demon rum: Billy Sunday -- "The great divide," Part I: William B. Riley -- "The great divide," Part II: Harry Emerson Fosdick -- "The most noticeable public religious voice": Charles E. Coughlin -- "A realist without despair, an idealist without illusion": Reinhold Niebuhr -- "The moral leader of our nation": Martin Luther King Jr. -- "Above all a preacher": William Sloane Coffin Jr. -- "America's pastor": Billy Graham -- An aptly named prophet: Jeremiah A. Wright Jr.
Includes bibliographical references and index.
Keywords: United States -- Church history; Christian biography -- United States; Sermons, American -- History and criticism; Christianity -- Influence; Christian biography; Christianity -- Influence; Sermons, American; United States; Church history; Criticism, interpretation, etc